UIFlex - uma ferramenta para a criação de um perfil de interação para a web adaptativa - Proença, Mailson de Queiroz (2017)
To address the diversity of users and the different interaction requirements, the user interfaces could be more flexible, being adapted according to each user profile. Currently, some web interfaces are already flexible, but this flexibility is usually made from explicitly made adjustments by the user in each website. The flexibility achieved by the interfaces of the current websites is not enough when the diversity of users and different interaction needs are considered. In addition, to adapt a web system, currently the user has to configure each system individually and not all users are aware of the different possibilities of presentation and configuration of the websites. Since the interfaces must be flexible to meet the different needs and diversity of users, this work aims to provide users with the possibility to adapt the websites according to their needs and preferences. To achieve this goal, an approach was formalized where the user defines his interaction profile, based on rules, guidelines and good design recommendations, and later this interaction profile is used to adapt the interfaces. In addition, the UIFlex tool was developed, where the user defines their interaction profile and, from this profile, the tool flexibilizes the interfaces of the websites that users navigate according to the interaction profile defined by the user. Finally, two evaluations were carried out in different scenarios: one face-to-face and the other online. These evaluations were carried out with the purpose of verifying the viability of the UIFlex tool and whether it meets the diversity of users. In both scenarios, users accessed certain websites with and without the UIFlex tool and subsequently answered questionnaires related to user satisfaction, website behavior and interaction efficiency. The results of the questionnaires answered indicated that the UIFlex tool brings benefits during the interaction of the users with the websites, mainly related to the efficiency, due to the adaptation made in the websites by the tool, without the need to configure each website individually. With the studies carried out and with the analysis of the answers of the questionnaires it is concluded that the UIFlex tool contributed positively to the users adapting the interfaces of the websites according to their preferences and/or needs.